GENDERS PATTERNS ON FACEBOOK: A JORDANIAN SOCIOLINGUISTIC PERSPECTIVE - Hythem Wanas Al-Sad; Kamariah Yunus (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2024)
The emergence of social media has demonstrated impacts on Jordanian males’ and females’ culture and language. These impacts highlighted the differences between women’s and men’s usage patterns on social media that have been a subject of interest to scholars. Jordanian culture is bounded by values, traditions, and norms from Islam and Arabic values. Thus, the present study aims to figure out gender prototypes on social networking sites, namely Facebook, taking Jordan society as the norm. It also investigates how much Fakebook’s use has changed males’ and females’ social, cultural, and linguistic behaviors. The study is a mixture of sociolinguistic and anthropological research as both language and culture are studied. Discourse and thematic analysis were performed to analyze the collected data from 80 Facebook active users whose ages range from 19 to 45 (40 male and 40 female). The results showed the differences between males and females users at different levels. Females tend to use informal language to comment on females’ posts and formal language to comment on males’ posts. Further, most males explicitly use their real images as profile pictures, while females hide their real pictures. Females disclose their real names on their profiles just as males, but females tend to hide their contact information due to privacy concerns. Females and males are almost the same in using Facebook for social purposes, either in topics or groups. The results can be interpreted as reflections of Jordanian culture and social values that shape women’s and men’s positions and attitudes in Jordanian communities. This study recommends further research on social networks, considering other social variables such as education, age, and geography to pinpoint the exact patterns of users that are relatively diverse according to the speech communities.